2006
DOI: 10.1002/dmrr.704
|View full text |Cite
|
Sign up to set email alerts
|

The C‐peptide fragment EVARQ reduces glomerular hyperfiltration in streptozotocin‐induced diabetic rats

Abstract: The present study shows that administration of the C-peptide fragment EVARQ has similar effects on GFR and blood glucose levels as the intact C-peptide molecule, suggesting at least one active site within this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…Our results from conscious rats confirm previous findings that the early onset of STZ-induced diabetes in rats results in glomerular hyperfiltration 16 , which is reversed by C-peptide administration 10 . These results clearly show that the applied method is suitable for detecting physiologically relevant changes in GFR in rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results from conscious rats confirm previous findings that the early onset of STZ-induced diabetes in rats results in glomerular hyperfiltration 16 , which is reversed by C-peptide administration 10 . These results clearly show that the applied method is suitable for detecting physiologically relevant changes in GFR in rats.…”
Section: Discussionsupporting
confidence: 92%
“…C-peptide is secreted from the islets of Langerhans together with insulin in equimolar amounts, and has been shown to influence physiological processes 7 . Several studies have also shown renoprotective effects of exogenous C-peptide administration to patients with type-1 diabetes 8,9 , but also to animals with experimental insulinopenic diabetes 9,10 . Such beneficial effects include decreased glomerular hyperfiltration, albuminuria, renal hypertrophy, and normalized glomerular volume 11 .…”
Section: Introductionmentioning
confidence: 98%
“…Infusion of C-peptide over 2 wk in STZinduced diabetic rats in the absence of insulin also prevents glomerular hyperfiltration as well as glomerular hypertrophy and microlabuminuria (87). Similar beneficial effects following treatment with several different doses of either full-length C-peptide or with its active COOH-terminal fragment EVARQ were observed in other studies using STZ-induced diabetic rats (43,74,88,99). Effects of C-peptide have also been studied in humans during early stages of diabetic nephropathy.…”
Section: Effects Of C-peptide In the Diabetic Kidneysupporting
confidence: 54%
“…However, despite overall improvements in treatment, diabetic nephropathy remains associated with high morbidity and mortality, indicating the need for the development of novel treatments, and in recent years, C-peptide has started to emerge as a potential novel therapeutic treatment for type 1 diabetesassociated end-organ complications, including diabetic nephropathy (43,47,74,88,99). This part of the review will focus on describing the mechanisms by which C-peptide is thought to protect the diabetic kidney.…”
Section: Effects Of C-peptide In the Diabetic Kidneymentioning
confidence: 99%
“…Elegant studies by Nordquist et al [22] recently suggested a novel mechanism by which C-peptide may exert its beneficial effects on GFR. The protective effect, mediated by constriction of the afferent glomerular arteriole, net dilation of the efferent arteriole and inhibition of tubular Na + , reabsorption requires the C-terminal EVARQ fragment of C-peptide [23]. …”
Section: Role For C-peptide In Alleviating the Complications Of Diabementioning
confidence: 99%